The Islington crime survey: thirty years on, 2016 (UK Data Service, 2018)
This research aimed to provide an overview of the trends in crime and victimisation in an inner city area over the last thirty years. In this period it is widely recognised that the inner city has undergone major changes involving significant population shifts. The London Borough of Islington is taken as a point of reference because it exhibits significant changes in the composition of its population over the last thirty years as well as experiencing major changes in its leisure and consumer activities. At the same time it includes an interesting mix of gentrified areas combined with pockets of poverty and deprivation. The principal aim of the research was to examine changes in the distribution of crime and victimisation in this particular context. In 1986 a landmark study of crime and victimisation was carried out and published in the form of The Islington Crime Survey (Jones, McLean and Young, 1986). This study sought to both extend and qualify the findings of the then British Crime Survey (currently referred to as the Crime Survey for England and Wales) which collected national data. It was recognised that the form and level of crime varies significantly by area and that if victimisation surveys are going to inform policy then they have to be detailed and localised. For example, local crime surveys like The Islington Crime Survey (ICS) are able to identify specific streets and areas where people feel unsafe and can provide policy makers with the information that allows them to make such areas safer. They also allow assessments by residents of police performance and the opportunity for residents to express their priorities and concerns. Nationally, there has been a significant decrease in most forms of recorded crime over the last two decades. This research provided an investigation of this decrease in an inner city area and aimed to identify which groups, if any, have benefited from this decrease. The survey also looked at repeat victimisation since it is known that some of the most victimised groups tend to be repeatedly victimised, with the aim to see if these levels of repeat victimisation have increased or decreased over time. One of the main aims of the survey was to gain information of the experiences of victimisation amongst different ethnic groups and also to examine their relation with the police. There is also a focus on domestic violence, fear of crime, as well as forms of commercial crime. The research also drew on other data sources that provide information on crime in the borough that have been produced over the past thirty years in order to identify trends. The identification of these trends are in turn linked to an analysis of the changing economic and social context in which they are taking place. In this way the research examined changes in the distribution of victimisation in relation to the changing social composition and economic activity in the borough. This form of analysis should be able to say something significant about the changing nature of urban life and about people's concerns and experiences, which should provide some useful insights into the changing dynamics of urban culture. There is considerable debate by academic researchers about the nature and direction of urban change and in particular how these changes relate to crime. There are also debates about the degree to which various crime prevention measures have been effective in reducing crime. By identifying urban trends in conjunction with changing patterns of crime this research provides a unique opportunity to increase our understanding of some of the most significant developments that are taking place in contemporary society. The survey was undertaken using a face-to-face Computer Assisted Personal Interviewing (CAPI) methodology, with interviews being conducted in respondents’ homes. To qualify as a ‘victim’ for the purposes of the study, a respondent needed to have experienced one of the particular crime types that were in scope for the study, and to have done so in the period between the start of 2015 and the time of the interview. 2,000 interviews were targeted in total (1,500 interviews with victims and 500 interviewers with non-victims).